High Performance Computing in Science and Engineering 2000: Transactions of the High Performance Computing Center Stuttgart (HLRS) 2000 - Krause, Egon; Jäger, Willi (Springer, 2001)
Spinodal Decomposition in Binary Polymer Blends: Monte Carlo Simulations and Dynamic Mean Field Theory -- Dynamics of Convection and Dynamos in Rotating Spheres -- Recent Developments in IMD: Interactions for Covalent and Metallic Systems -- Finite Difference Modelling of Seismic Wave Phenomena within the Earth’s Upper Mantle -- Collisional Dynamics of Black Holes and Star Clusters Using Massively Parallel Computing -- Three-Dimensional Direct and Inverse Electromagnetic Scattering -- Precession Driven Flow in Ellipsoidal Cavities -- The Computation of Highly Exited Hyperbolic 3D-eigenmodes and its Application to Cosmology -- Fluid Jet Simulations using Smoothed Particle Hydrodynamics -- Spectral Properties of CUO2 Planes in a Cluster Perturbation Approach -- Electronic, Structural and Vibrational Properties of Chalcogenides on Si(001) and Ge(001) Surfaces -- Dynamical Properties of the t-J Model -- Effects of Three Nucleon-Interactions in A = 4 -- Phase Transitions in Insulating 1D Electron Systems -- Excited States of Semiconductors and Molecules -- Jacobi-Davidson Algorithm with Fast Matrix-Vector Multiplikation on Massively Parallel and Vector Supercomputers -- Time-dependent Reactive Scattering for Ion-neutral Collisions -- Ground and Exited States of the Hydrogen Negative Ion and Negative Donor Systems in Strong Magnetic Fields -- Quantum Chemical Calculations of Transition Metal Complexes -- Car-Parrinello Density Functional Calculations of the Bond Rupture Process of Thiolate on Gold in AFM Measurements: Progress and First Results -- DNS of Laminar-Turbulent Transition in a 3D Aerodynamics Boundary-Layer Flow -- High-Performance Computing: Numerical Simulation of the Melt Flow in an Industrial Czochralski Cruzible -- Analysis of an Elastic Wing in Subsonic Flow Using Direct Numerical Aeroelastic Simulation -- Large Eddy Simulation of the Flow over a Matrix of Surface-mounted Cubes -- Simulation of Bubbly Gas-Liquid Flows by a Parallel Finite-Difference /Front-Tracking Method -- Rotary Wing Aerodynamics and Aeroelasticity -- Unsteady Flow Simulations for Turbomachinery Applications on Dynamic Grids -- Testing Turbulence Models by Comparison with DNS Data of Adverse-pressure-gradient Boundary Layer Flow -- Large Eddy Simulation of Subcritical Flow around Sphere -- LES of Turbulent Flows Trough 90°-Pipe Bends on NEC SX-4 -- Computations for the European LESFOIL Project -- Correlation Analysis of Permixed Turbulent Flames Using Direct Numerical Simulations -- Adaptive Chemistry Computation to Accelerate Parallel DNS of Turbulent Combustion -- The Generation of Dissipative Quasi-Particles near Turing’s Bifurcation in Three-Dimensional Reacting Diffusion Systems -- Upwind Relaxation Algorithm for Reentry Nonequilibrium Flows -- Numerical Simulation of the Coupled Dynamic Processes of the Water-Steam Cycle and the Furnace System -- Container Size Dependence of the Velocity Fluctuations in Suspension of Monodisperse Spheres -- Implementing Luby’s Algorithm on the CRAY T3E -- Spatial Partitioning for Parallel Hierarchical Radiosity on Distributed Memory Architectures -- Construction of Large Permutation Representations for Matrix Groups on Parallel Supercomputers -- Advances in High-Performance Computing: Multigrid Methods for Partial Differential Equations and its Applications -- Recent Advances of SKaMPI -- Porting SPLASH-2 Benchmarks to the T3E.